Modality Realization in Covid-19 Academic Papers - Aulia Ukhtin; T. Silvana Sinar; Thyrhaya Zein (Mimbar Ilmu, 2023)
Modalities are often used in both spoken and written material. However, people only know the modalities and values manifested in academic written texts once they conduct a study. This research aims to analyze the form and matter of modalities and investigate how these modalities are realized in Covid-19 scholarly articles. This research uses descriptive qualitative research methods and Halliday's theory. The data consists of clauses of six COVID-19 social and political journal articles on various topics, such as (social, economic, political, health, communication, and tourism). Data collection was carried out using a documentary approach. The model used in this research is interactive. The data analysis technique uses qualitative descriptive analysis. Based on the findings of this research, 260 clauses contain modality, and two types of modality are used in them. This research also found the realization of modality as a capital operator that is often used in Covid-19 academic papers, as it is. Found 238 capital operators. Apart from that, authors generally use limited modal operators in their articles because there are 238 modal operators located, and this is followed by additional modals with a total of 18. On the other hand, passive verb predicators and adjectives are rarely found.